2014
DOI: 10.3109/02699206.2014.926994
|View full text |Cite
|
Sign up to set email alerts
|

Speech-language pathologists’ practices regarding assessment, analysis, target selection, intervention, and service delivery for children with speech sound disorders

Abstract: A survey of 231 Australian speech-language pathologists (SLPs) was undertaken to describe practices regarding assessment, analysis, target selection, intervention, and service delivery for children with speech sound disorders (SSD). The participants typically worked in private practice, education, or community health settings and 67.6% had a waiting list for services. For each child, most of the SLPs spent 10-40 min in pre-assessment activities, 30-60 min undertaking face-to-face assessments, and 30-60 min com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(97 citation statements)
references
References 68 publications
7
88
1
1
Order By: Relevance
“…Surveys of paediatric speech and language therapists (SLTs) indicate that children with SSD comprise more than 40% of clinicians’ caseloads, with over 40 000 children in the UK referred annually (Broomfield and Dodd 2004b, Joffe and Pring ). This trend is also apparent internationally, with SLTs in Australia, the United States and the Netherlands indicating that children with SSD form nearly half a typical caseload (McLeod and Baker , Brumbaugh and Smit , Priester et al . ).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Surveys of paediatric speech and language therapists (SLTs) indicate that children with SSD comprise more than 40% of clinicians’ caseloads, with over 40 000 children in the UK referred annually (Broomfield and Dodd 2004b, Joffe and Pring ). This trend is also apparent internationally, with SLTs in Australia, the United States and the Netherlands indicating that children with SSD form nearly half a typical caseload (McLeod and Baker , Brumbaugh and Smit , Priester et al . ).…”
Section: Introductionmentioning
confidence: 93%
“…, Joffe and Pring , McLeod and Baker ). In Australia, these surveys have shown that parents are involved in a range of intervention tasks, including observing the SLT providing intervention and directly providing intervention to their child (McLeod and Baker , Watts Pappas et al . ).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies demonstrate that it is important to analyze different groups of judges in terms of speech disorders, since the incidence of speech sound disorders is significantly high, and the diagnosis is often not adequate or not provided early on, which may not only impair speech, but also learning, social interactions, among others 26,27 . The findings of this study suggest that the degree of perception of intelligibility between (non-professional) men and women who do not have daily contact with children, let alone children with speech sound disorder, is similar, but women in this group agreed more, since they have sharper perceptual-auditory skills, and, thus, would be able to analyze speech in a more detailed and accurate manner 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Single word picture-naming tasks are commonly used by speech-language pathologists (SLPs) to assess children's speech (McLeod & Baker, 2014). An important component of any sampling task is the capacity to measure a range of possible phonological errors across a sample of word positions, in a relatively short period of time (Eisenberg & Hitchcock, 2010;Kirk & Vigeland, 2015).…”
Section: Assessment Of Polysyllabic Wordsmentioning
confidence: 99%